Art and Mindfulness Behind Bars: Examples From Wyoming Prison-Based Courses on Memoir and Stoic Philosophy. (September 2019) - Dewey, Susan; Muthig, Alec J.; Colter, Robert S.; Brock, Katy
In this self-reflective piece, the coauthors critically engage with their experiences using arts-based and mindfulness practices with incarcerated women and men and university students. We offer insights derived from teaching two separate arts-based courses in prison. The first focused on memoir-writing, a unique storytelling form in which a writer's experiences take center stage. The second involved engaging with philosophy to discover more effective ways of living. The experiences of all concerned in these two classes emphasized the power of arts-based and mindfulness education to transform lives, both within and outside prison walls.